ISLAMIC EDUCATION TEACHERS' CREATIVE STRATEGIES IN DEVELOPING CRITICAL THINKING OF GRADE VIII B STUDENTS AT MTS DARUTTHOLIBIN - Stania Rahmah; Faisal kamal; Ali Imron (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2026)
Teacher-centered learning that emphasizes memorization often limits students’ critical thinking and active participation. In Islamic Religious Education, students tend to become passive learners, making creative teaching strategies necessary to encourage critical thinking and active engagement. This study examines the creative strategies employed by Islamic Religious Education teachers in developing the critical thinking skills of class VIII B students at MTs Darutholibin Watumalang Wonosobo. The study was motivated by teacher-centered learning practices that emphasize memorization and limit students’ active involvement in higher-order thinking processes. This research used a qualitative approach with a descriptive design. Data were collected through interviews, observations, and documentation, while data validity was tested using source and method triangulation. The data analysis process included data reduction, data presentation, and conclusion drawing. The findings revealed that teachers implemented creative learning strategies through a flexible combination of lectures, contextual approaches, and discussions. Lectures were used to deliver fundamental concepts, contextual approaches connected learning materials with students’ real-life experiences, and discussions encouraged active participation and idea exchange. The implementation of these strategies contributed to increased student activity, confidence in expressing opinions, and the ability to analyze and relate learning materials critically. However, the improvement in students’ critical thinking skills was not evenly distributed, as it was influenced by factors such as learning motivation, self-confidence, and the surrounding learning environment.